Marketing management - Miranda-Gow, Carmelita; Miranda, Gregorio S. (Mandaluyong City, Philippines : National Book Store, 1990)
Discussions found in this book center around marketing decision-making.
CHAPTER 1. Introduction -- 2. Marketing and it's environment -- 3. Focus on the consumer -- 4. Marketing Research -- 5. Devising a marketing plan -- 6. Product Planning and Development -- 7. Market and customer -- 8. Industrial Marketing -- 9. Channels of distribution -- 10. Brands and Branding policies -- 11. Package and packaging policies -- 12. Advertising and sales promotion -- 13. Price and Pricing policies -- 14. Sales Management -- 15. Selling Policies and Practices -- 16. Stock control and inventory -- 17. International Marketing.
Includes bibliographical references.
Keywords: MARKETING